2020
DOI: 10.1096/fj.201902584r
|View full text |Cite
|
Sign up to set email alerts
|

Advances in histone demethylase KDM4 as cancer therapeutic targets

Abstract: The KDM4 subfamily H3K9 histone demethylases are epigenetic regulators that control chromatin structure and gene expression by demethylating histone H3K9, H3K36, and H1.4K26. The KDM4 subfamily mainly consists of four proteins (KDM4A‐D), all harboring the Jumonji C domain (JmjC) but with differential substrate specificities. KDM4A‐C proteins also possess the double PHD and Tudor domains, whereas KDM4D lacks these domains. KDM4 proteins are overexpressed or deregulated in multiple cancers, cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 203 publications
(486 reference statements)
0
75
0
Order By: Relevance
“…Histone demethylation involves modification of chromatin formation and is a crucial component in the construction of protein complexes controlling gene expression. Histone demethylation enzymes have been proved to be frequently involved in tumor development 12 . Previous study has reported that KDM4A could promote malignant proliferation of human liver cancer cell line Hep3B, which was consistent with our findings 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone demethylation involves modification of chromatin formation and is a crucial component in the construction of protein complexes controlling gene expression. Histone demethylation enzymes have been proved to be frequently involved in tumor development 12 . Previous study has reported that KDM4A could promote malignant proliferation of human liver cancer cell line Hep3B, which was consistent with our findings 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Among genes which both had a strong binding signal of RFX5 in the promoter region and were closely correlated with RFX5 in RNA expression level ( Fig. 2A), KDM4A had engrossed our attention due to its reported role in several cancers 12 , including HCC 13 . Hence, we decided to focus on the regulation of RFX5 on KDM4A expression in HCC cells.…”
Section: Rfx5 Binds the Promoter Region Of Kdm4a In Hcc Through Analmentioning
confidence: 98%
“…KDM4 proteins, like Gis1, are responsive to nutritional and metabolic signals, in part due to their requirement for α-ketoglutarate (AKG), Fe 2+ , and O 2 for activity [17][18][19][20][21]. KDM4 proteins play important roles in diverse biological processes, and their altered expression or function has been implicated in multiple cancers, cardiovascular diseases, and mental retardation [8,15,[85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…For some enzymes, for example, TET2 and the KDM4 sub-family, their role is relatively clear-cut. KDM4A-D are over-expressed in a wide variety of tumour types, and are therefore suggested to play a pro-tumourigenic role in cancer (reviewed in [109]). In contrast, TET2 is thought to be a tumour suppressor, and is either mutated or dysregulated in multiple cancers, particularly haematological malignancies.…”
Section: Og-oxygenases: Disease Mediatorsmentioning
confidence: 99%
“…Therapeutic KDM4 inhibitors are also of interest, given the proposed role for the KDM4 sub-family in promoting tumour growth. However, the development of potent and selective inhibitors has been challenging [109]. Stringent specificity for such inhibitors is paramount, particularly as 2OG-oxygenases have wide-ranging cellular roles.…”
Section: Inhibitionmentioning
confidence: 99%